Missed opportunity for tuberculosis screening and prevention and the associated factors among child contacts in rural southwestern Uganda - Martin Mbabazi Mpimbaza; Richard Migish; Godfrey Twesigomwe; Francis Bajunirwe (BMC Pulmonary Medicine, 2025)
Background: Tuberculosis (TB) treatment and control guidelines recommend screening of contacts of bacteriologically confirmed TB cases and prompt initiation of preventive therapy. However, many children exposed to TB in high-burden settings like Uganda remain unscreened. The extent of the missed opportunity for screening TB-exposed children in Ugandan rural settings remains largely unknown. We determined the burden and associated factors of missed opportunity for TB screening and prevention in rural southwestern Uganda. Methods: We conducted a cross-sectional study in four high-volume TB treatment centers in Kanungu District, southwestern Uganda. Using consecutive sampling, we included children aged 0–14 years who were household contacts of bacteriologically-confirmed persons with TB. We defined a missed opportunity as not being screened for TB or not receiving preventive TB treatment despite being eligible. We used modified Poisson regression to identify factors associated with the missed opportunities. Results: Among 279 children enrolled from 79 households, 119 (42.7%) were aged < 5 years, 103 (36.9%) were 5–10 years, and 57 (20.4%) were 11–14 years. Overall, 140 (50.2%) were never screened. Of the 139 screened, 25 (18.0%) reported TB symptoms and 6 (24.0%) of these received TB treatment; among the 19 symptomatic but untreated, 3 (15.8%) missed isoniazid preventive therapy (IPT) initiation. Of 114 asymptomatic contacts, 60 were IPT-eligible, yet 34 (56.7%) were not initiated on IPT. Overall, 177/279 (63.4%; 95% CI: 67.6–68.9%) experienced a missed screening or prevention opportunity. Factors independently associated with missed opportunity were living in a household below the poverty line (adjusted prevalence ratio [aPR] = 1.62, 95% CI: 1.19–2.21), lack of formal education among index patients (aPR = 1.41, 95% CI: 1.09–1.83), and being a contact aged < 5 years (aPR = 1.45, 95% CI: 1.12–1.88). Conclusion: Our study revealed a high burden of missed opportunity for TB screening and prevention among child contacts in this rural setting, driven by socio-economic disadvantages, including household poverty, lack of formal education, and younger age for household TB contacts (< 5 years). Interventions should target socio-economically disadvantaged households to improve access to TB screening and preventive care.
Keywords: Tuberculosis; Contact tracing; Pulmonary; Child; Uganda